A case study of the technique used to increase skiing velocity in female cross-country skiers, focusing on the V2 skate in the flight phase - Fujita, Z.; Yoshioka, S.; Ishige, Y.; Tauchi, K.; Tsuchiya, J. (Japan Journal of Physical Education, Health and Sport Sciences, 2012)
The aim of this study was to clarify how coaching in the V2 skate technique, intentionally including the flight phase, affects the skating velocity of female cross-country skiers. First, seven female skiers performed the V2 skate technique at maximal effort. Next, five subjects who did not have any flight phase in their V2 skate technique were trained to perform it along with the flight phase for about 10 minutes, and were then asked to execute the flight phase. In this test, the subjects used poles and skis equipped with force sensors, and their velocity was recorded. After the test, each subject was interviewed about her subjective experience of the V2 skate including the flight phase. It was found that the training caused all of the subjects to change the V2 skate so that it included the flight phase. Moreover, during skating attempts with the flight phase, both the skating velocity and the peak and average forces of the pole and ski increased significantly. The interviews revealed that three subjects felt a sense of fear when they were airborne, and that four subjects felt close to loss of balance. These results suggest that training in the V2 skate with a flight phase was effective for increasing the skating velocity of the female skiers. Moreover, it was evidently difficult for the female skiers to learn to skate with flight phases through a normal training method because of the sense of fear they experienced during the maneuver.